Dampak Judi Online Terhadap Kalangan Remaja (Studi Kasus Tebing Tinggi) - Dika Sahputra; Anisya Afifa; Adinda Muna Salwa; Nurman Yudhistira; Liyani Azizah Lingga (Institut Agama Islam Negeri Curup, 2022)
This research is motivated by the rise of online gambling in the community, especially among teenagers. Online gambling has a lot of negative impacts on the perpetrators, so this study will discuss the impact of online gambling on teenagers in Tebing Tinggi City. The method used in this study is a qualitative method with descriptive data analysis, by conducting in-depth interviews with five teenagers in Tebing Tinggi City and exploring all sources related to the impact of online gambling. Adolescence is commonly referred to as the transition period from childhood to adulthood. Where in this period of adolescence, they want to show their existence, one of which is by joining in doing various things for the sake of satisfaction and pleasure, regardless of the impact that will occur. Online gambling is included in deviant behavior that exists in the community and most of those who play it are teenagers. Teenagers initially play online gambling out of curiosity and want to join in, but this can make them addicted because of the hope of winning. The results of this study indicate that online gambling has a lot of negative impacts. Among them are the social impact, namely being lazy to get along, the material impact, namely if they experience defeat, their money will run out, the religious impact, namely they will neglect to worship because they play online gambling, and the achievement impact, namely their learning achievement will decrease because they are lazy to study due to online gambling.